The strategic management of literacy learning in inclusive primary school in Malang - Nawasita, Kartika Dwi; Timan, Agus; Sultoni, Sultoni (Journal of Research in Instructional, 2023)
This research aims to investigate strategic management related to literacy learning implemented by inclusive primary schools in Malang, covering (1) The formulation of vision and mission; (2) analysis of the internal and external environment that influences; (3) determination of goals, targets, and strategies; and (4) results and evaluation of the implementation of strategic management of literacy learning on reading, writing, and reading comprehension skills for students in inclusive elementary schools. Three inclusive primary schools in Malang were used for the qualitative method of this study. The principal of the school, the vice principal in charge of the curriculum and the teachers are the research subjects. Observations, interviews, and documentation shall be used for the collection of data. Data extraction, data presentation and conclusions are used to carry out the analysis. The results of the study indicate that (1) the development of literacy learning activities in inclusive schools is based on the development of a vision and mission, (2) the internal and external factors in inclusive primary schools have an impact on the development of literacy learning activities, (3) goals, objectives, and strategies for literacy learning in inclusive primary schools have been tailored to the diverse levels and needs of students, and (4) the results and evaluation of the implementation of literacy learning in inclusive primary schools enhance students' reading, writing, and comprehension skills through regular and systematic execution and evaluation.